Individual mortality and macro-economic conditions from birth to death - Maarten Lindeboom; France Portrait; Gerard J. van den Berg (Institute for the Study of Labor (IZA), 2003)
This paper analyzes the effects of macro-economic conditions throughout life on the individual mortality rate. We estimate flexible duration models where the individual?s mortality rate depends on current conditions, conditions earlier in life (notably during childhood), calendar time, age, individual characteristics, including individual socio-economic indicators, and interaction terms. We use individual data records from Dutch registers of birth, marriage, and death certificates, covering an observation window of unprecedented size (1812-1999). These are merged with historical data on macro-economic and health indicators. The results indicate a strong effect of macro-economic conditions during childhood on mortality at all ages. Those who are born in bad times on average have a high mortality rate throughout life, in particular during childhood itself and at ages above 50. Current macro-economic conditions mostly have an effect on youths and on the elderly.
Keywords: I1; C5; J1; N3; 330; death; longevity; health; business cycle; recession; life expectancy; lifetimes; epidemics; Sterblichkeit; Gesundheit; Konjunktur; Makroökonomischer Einfluss; Schätzung; Niederlande